Relationship of problem solving ways with the process of addiction in alcohol dependent patients - Demirbaş, Hatice; Özgür İlhan, İnci; Doğan, Yıldırım B. (Journal of Dependence, 2004)
Objective: In the present study it was aimed to investigate relationships between problem solving methods and their longest period of abstinence.Method: A total of 96 male patients diagnosed with alcohol dependence and attending an inpatient treatment program and hospitalized in any time between the dates October 2001 and October 2003 formed the study population. Problem Solving Inventory (PSI) has been applied. Relationships between duration of longest period of abstinence with subscale scores of PSI have been analyzed.Results: When the age variable was controlled, no statistically significant relationship was found between the duration of the longest period of abstinence and PSI subscale scores of alcohol dependent patients. It has been shown that alcohol dependent patients use problem solving confidence, impulsive, planfulness, monitoring and avoidant styles more frequently as they get older.Conclusion: No specific problem solving style can be suggested to be related to remission in alcohol dependent patients.
Keywords: Alcohol dependence; problem solving; abstinence